"Hanging Out" while Studying "Up": Doing Ethnographic Fieldwork in International Relations. Issue 4 (2nd March 2021) - Nair, Deepak
Abstract: This article advances a methodological argument on how to do ethnographic fieldwork amid social elites and inaccessible bureaucracies in international politics. Instead of participant observation or semi-structured interviews, the article proposes "hanging out" as an alternative strategy to generate immersion and ethnographic insight. While the ethnographer studying "down" is arguably always "hanging out" (the village as the exemplary mise-en-scene of this genre), this technique takes a more defined form when studying "up" elites. Specifically, hanging out when studying "up" is a strategy where the fieldworker commits to a period of continuous residence amid members of a community; engages in ludic, informal, and often sociable interactions outside or at the sidelines of their professional habitats; and participates in a range of activities where building rapport is as important as the primary goals of the research. I illustrate this methodological strategy and its payoffs by reflecting upon a year of fieldwork among the diplomats and bureaucrats of the Association of Southeast Asian Nations—an informal, quiet, and often sub rosa diplomatic project run by a band of mostly authoritarian states in Southeast Asia. This article contributes to debates on the viability of ethnographic fieldwork in international relations (IR); advances a methodological corrective to fieldwork prescriptions in new micropolitical studies of practice, interactions, and emotions in IR; and offers a practical illustration of what studying "up" looks like in diplomacy and international politics.